2016
DOI: 10.24953/turkjped.2016.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric langerhans cell histiocytosis: single center experience over a 17-year period

Abstract: The regression and relapse rates were 100% and 33% for SS-LCH. The regression and relapse rates were 73%, and 18% for MS-LCH. Two infants with MS-LCH died despite chemotherapy.Pulmonary and liver involvements affected outcome adversely in MS-LCH. Multidisciplinary treatment approaches are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 25 publications
2
17
0
Order By: Relevance
“…This study presents data on 66 consecutive patients with LCH, treated over a 45‐year period by a single reference centre, the Department of Pediatric Hematology‐Oncology of the ‘Aghia Sophia’ Children's Hospital in Athens. The male predominance was 1.5:1, which was consistent with previous studies that reported male:female ratios of 1.2–1.8:1 1,18,19 . Two‐thirds of our patients were diagnosed with single system LCH, mostly of the bone.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…This study presents data on 66 consecutive patients with LCH, treated over a 45‐year period by a single reference centre, the Department of Pediatric Hematology‐Oncology of the ‘Aghia Sophia’ Children's Hospital in Athens. The male predominance was 1.5:1, which was consistent with previous studies that reported male:female ratios of 1.2–1.8:1 1,18,19 . Two‐thirds of our patients were diagnosed with single system LCH, mostly of the bone.…”
Section: Discussionsupporting
confidence: 91%
“…This is consistent with previous results showing that single system LCH accounts for 42-69% of the total cases. 1,[18][19][20] The median age at diagnosis was significantly younger in patients with multisystem than single system LCH in our study (1.4 years vs.…”
Section: Discussionmentioning
confidence: 47%
See 1 more Smart Citation
“…Su et al [ 11 ] reported 100% 5-year survival in pediatric LCH patients when the disease involved only bone[ 11 ]. In a long-term (over 17 years) follow-up study of pediatric LCH, SS-LCH showed a 100% regression rate and low relapse vs 73% regression in MS-LCH[ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…LCH involving the skin, bone, lymph nodes or pituitary gland is considered “low-risk” because of its good response to treatment. Involvement of the lungs, hematopoietic system and spleen, and liver is considered “high risk” with an unfavorable outcome[ 1 , 6 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%